TERAPI BIOLOGIK PADA PASIEN PSORIASIS - Thaha, Athuf (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT Treatment limitations of current immunosuppressive therapies, and growing understanding of psoriasispathogenesis on a molecular level have stimulated much interest in the field of immunomodulatory therapy fomanagement of psoriasis. Genetic engineering has allowed the development of proteins that are targeted tospecific cell surface receptors. A well over 40 targeted biologic agents are in preclinical and clinical testing foT-cell mediated inflammatory diseases, including psoriasis. It is important that, as a doctor become weleducated in biologics, since several of these agents are available for the management of psoriasis. Keywords: immunosuppressive therapy, immunomodulatory therapy, genetic engineering, surface receptors, targetedbiologic agents, biologics.